Impacts of Parental Locus of Control on Indigenous Sami and Non-Sami Children’s Mental Health and Well-being in Norway - Antony, Celina (2023)
Background: Existing research overemphasizes issues of substance use and suicide in Indigenous populations, failing to address the key factors influencing Indigenous child mental health and well-being within the household. This study seeks to examine the impacts of parental locus of control (PLOC) on child mental health and well-being among Sami and non-Sami children in Norway. Methodology: Analyses of data from the Norwegian Mother and Child Cohort Study were conducted in three phases: 1) a cross-tabulation analysis examining the differences in PLOC between Sami and non-Sami parents, with a consideration for the child’s sex assigned at birth; 2) a multiple linear regression investigating how demographic, psychosocial, and cultural factors influence PLOC; and 3) a multiple linear regression assessing how PLOC affects mental health and well-being among Sami and non-Sami children in Norway, with a consideration for the child’s cultural context and sex assigned at birth. Results: Although both groups leaned more towards internal PLOC overall, Sami mothers remained closer to external PLOC than non-Sami mothers. One of four items measuring maternal depression and three of four items measuring maternal self-esteem were statistically significant predictors of PLOC. PLOC was found to be a statistically significant indicator of children’s emotionality at 3 and 5 years, and sociability at 3 years. Children’s sex assigned at birth was a statistically significant predictor of shyness at 3 years, with boys experiencing higher levels of shyness than girls. Conclusion: Cultural distinctions, sex and gender, and maternal self-esteem play a crucial role in the child-rearing approaches employed and their effectiveness in promoting children’s social and emotional development in Norway. Research examining the association between maternal mental health and child-rearing approaches, as well as the impacts of PLOC on other aspects of children’s mental health and well-being, is necessary to inform mental health and social supports for ...